2015
DOI: 10.18775/ijied.1849-7551-7020.2015.11.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing university –industry collaboration: What are the drivers of academic researchers’ involvement in industry?

Abstract: Industry engagement of researchers plays an important role in organizational outcomes such as increased number of licenses and patents, innovation, successful R&Ds and consequently increased efficiency and economic performance. The gap between the theory and practice of industry engagement are identified and a scientific model of industry engagement of is developed in this paper. The research model depicts the possible generation of the industry engagement as an outcome. Through a detailed review of all factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…The above runs counter to the studies of Galid (2015) and Soendergaard (2015). They argue that economic incentives, recognition, networking, access to resources, industry problem-solving, research application (Ahamed Galib et al, 2015), organizational incentives, attitude towards collaboration, and intentions for participation (Soendergaard et al, 2015) are the main drivers promoting joint UIC activities (Mahdad et al, 2020(Mahdad et al, , 2018Perkmann et al, 2021). Regarding the consequences of UIC joint activities, our study found that such joint undertakings in emerging contexts occur mostly informally and aim to solve a social problem.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 62%
“…The above runs counter to the studies of Galid (2015) and Soendergaard (2015). They argue that economic incentives, recognition, networking, access to resources, industry problem-solving, research application (Ahamed Galib et al, 2015), organizational incentives, attitude towards collaboration, and intentions for participation (Soendergaard et al, 2015) are the main drivers promoting joint UIC activities (Mahdad et al, 2020(Mahdad et al, , 2018Perkmann et al, 2021). Regarding the consequences of UIC joint activities, our study found that such joint undertakings in emerging contexts occur mostly informally and aim to solve a social problem.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 62%